Antibody 10-1074 suppresses viremia in HIV-1-infected individuals - Caskey, Marina (Nat Med, 2017)
Monoclonal antibody 10-1074 targets the V3 glycan supersite on the HIV-1 envelope protein. It is among the most potent anti-HIV-1 neutralizing antibodies isolated to date. Here we report on its safety and activity in 33 subjects who received a single intravenous infusion of the antibody. 10-1074 was well tolerated with a half-life of 24.0 days in uninfected and 12.8 days in HIV-1-infected subjects. 13 viremic subjects received the highest dose of 30 mg/kg 10-1074. 11 of these participants were 10-1074-sensitive and showed a rapid decline of viremia by a mean of 1.52 log(10) copies/ml. Virologic analysis revealed the emergence of multiple independent 10-1074-resistant viruses within the first weeks after infusion. Emerging escape variants were generally resistant to the related V3-specific antibody PGT121, but remained sensitive to antibodies targeting non-overlapping epitopes, such as the anti-CD4 binding site antibodies 3BNC117 and VRC01. The results demonstrate the safety and activity of 10-1074 in humans and support the idea that antibodies targeting the V3 glycan supersite may be useful for treatment and prevention of HIV-1 infection.